“I sometimes feel like I can’t win!”: An exploratory mixed-methods study of women’s body image and experiences of exercising in gym settings - Emma S. Cowley; Jekaterina Schneider (PLoS ONE, 2025)
Despite an increase in gym memberships, women are less active than men and little is known about the barriers women face when navigating gym spaces. This study explored women’s body image and experiences exercising in gyms. Two-hundred and seventy-nine women (84% current gym-goers; 68.1% White) completed an online mixed-methods survey. Thematic analysis of qualitative data produced four themes and nine subthemes: (1) “Never enough” ([perceived] judgement about appearance, [perceived] judgement about performance); (2) “Often too much” (self-criticism, clothing challenges); (3) “Always on display” (harassment and safety, fighting for space, the appearance contingency); and (4) “Sometimes empowered” (empowering places, empowering self). Qualitative and quantitative data showed that women often feel judged for their appearance and performance, leading to a persistent sense of inadequacy, as well as having to fight for space in the gym and to be taken seriously, while navigating harassment and unsolicited comments from men. Despite this, women showed signs of resistance towards gendered and appearance ideals permeating gym environments and some experienced empowerment through skill acquisition, breaking gender norms, and exercising in supportive environments. Based on our findings, we suggest a multi-level approach to tackling these barriers and creating more inclusive gym spaces for women.